EXECUTORY POWER OF SETTLEMENT FOR FICTITIOUS CREDIT DISPUTES IN THE BANKING SECTOR THROUGH A MEDIATION APPROACH - Muhammad Yusuf Nur Saifuddin; Adhiningdyah Mulyani Taufiqs; Mahmud (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The development of Islamic banking in Indonesia brings various challenges, one of which is the emergence of fictitious credit practices that can cause financial losses and damage public trust in Islamic financial institutions. Fictitious credit occurs when a debtor applies for financing using problematic documents and unauthorized collateral, resulting in losses for the bank. In this case, Debtor X submitted nine forms of collateral, consisting of six primary collaterals and three additional collaterals, which were later proven to belong to other parties. This situation led to a legal dispute because the collateral could not be executed. Through court-facilitated mediation, the parties reached an agreement to replace the three problematic collaterals with a new single collateral: land located in Purbalingga. This agreement was recorded in a deed of settlement, which holds executory power equivalent to a legally binding court decision. The research results show that settlement through mediation is more effective than litigation, as it is faster and more cost-efficient, while also aligning with sharia principles, namely ishlah (reconciliation). With the deed of settlement, the bank has a clear legal basis to execute the new collateral if the debtor defaults again.